Orofacial Mycoses in Coronavirus Disease-2019 (COVID-19): A Systematic Review - Lakshman P. Samaranayake; Kausar S. Fakhruddin; Hien C. Ngo; H.M.N.M. Bandara; Y.Y. Leung (Elsevier, 2022)
Objectives: Studies reviewing orofacial mycoses in coronavirus disease-2019 (COVID-19) caused by severe acute respiratory syndrome 2 (SARS-CoV-2) infection are sparse. Here we review the major oral and maxillofacial mycoses of COVID-19, the associated comorbidities, and the probable precipitating factors. Methods: English-language manuscripts published between March 2020 and October 2021 were searched using PubMed, OVID, SCOPUS, and Web of Science databases, using appropriate keywords. Results: We identified 30 articles across 14 countries, which met the inclusion criteria of PRISMA guidelines. These yielded a total of 292 patients with laboratory-confirmed COVID-19, 51.4% (n = 150) of whom presented with oral and maxillofacial fungal infections, mainly comprising candidosis, mucormycosis, and aspergillosis. Candida infections were the most prevalent, present in 64% (n = 96), followed by mucormycosis, and only a single case of aspergillosis was noted. Oral and maxillofacial mycoses were predominantly seen in those with comorbidities, especially in those with diabetes (52.4%). Oral mucormycosis was noted in 8.6% (n = 13) and mainly manifested on the hard palate. An overall event rate of oral/maxillofacial mucormycosis manifestation in patients with COVID-19 with diabetes mellitus type 1/2 was about 94% (49/52; 95% confidence interval, 0.73%-0.89%), implying a very high association between diabetes mellitus and the latter condition. All fungal infections appeared either concurrently with COVID-19 symptoms or during the immediate recovery period. Conclusions: SARS-CoV-2 infection-related immunosuppression, steroid therapy, as well as comorbidities such as diabetic hyperglycemia appear to be the major predisposing factors for the onset of oral and maxillofacial mycoses in patients with COVID-19 across all age groups.